Primary granulocytic sarcoma of larynx. Issue 3 (13th November 2014) - Kim, Luke Y.; Purkey, Michael T.; Patel, Mihir R.; Ghosh, Ankona; Hartner, Lee; Newman, Jason G.; Chen, Amy
Abstract Background Granulocytic sarcoma is an extramedullary tumor of myeloblasts. The purpose of this report was to present a case of a primary laryngeal granulocytic sarcoma and review of the literature. Methods A literature review was performed using Medline and PubMed databases to search for cases of all primary and secondary myelogenous tumors of the larynx. Results A 36‐year‐old man presented with a mass involving the preepiglottic space that was histologically confirmed as an extramedullary acute myeloid leukemia, or granulocytic sarcoma. Our review found 18 cases of secondary involvement of the larynx by myelogenous tumors, and only 1 previously reported case of primary laryngeal granulocytic sarcoma. Conclusion The detection of granulocytic sarcoma is difficult given its rarity and nonspecific presentation. To our knowledge, this is the second reported case of primary granulocytic sarcoma of the larynx reported in the literature. © 2014 Wiley Periodicals, Inc. Head Neck 37: E38–E44, 2015